2018
DOI: 10.1016/j.ajpath.2017.10.024
|View full text |Cite
|
Sign up to set email alerts
|

A Large Set of miRNAs Is Dysregulated from the Earliest Steps of Human Hepatocellular Carcinoma Development

Abstract: Hepatocellular carcinoma (HCC) typically results from a stepwise process characterized by the development of premalignant lesions, such as low- or high-grade dysplastic nodules (LGDNs and HGDNs, respectively), in a cirrhotic setting. MicroRNAs (miRNAs) are small noncoding RNAs involved in post-transcriptional regulation of gene expression that can act as oncogenes or tumor suppressors. Whether and which miRNAs are involved in the early stages of HCC development remains elusive. Here, small-RNA sequencing was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…, 2017 ). Interestingly, small-RNA sequencing has revealed several miRNAs that are highly overexpressed in patient hepatocellular carcinoma (HCC) samples relative to cirrhotic nodules, including miR-24-3p with a more than sevenfold increase in expression ( Sulas, Di Tommaso, Novello, et al. , 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…, 2017 ). Interestingly, small-RNA sequencing has revealed several miRNAs that are highly overexpressed in patient hepatocellular carcinoma (HCC) samples relative to cirrhotic nodules, including miR-24-3p with a more than sevenfold increase in expression ( Sulas, Di Tommaso, Novello, et al. , 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is well recognized that these small non-coding RNAs involve in post-transcriptional regulation of gene expression and many cellular processes such as growth, angiogenesis, differentiation and metastasis [6]. Recent data have demonstrated that miRNA deregulation are already detectable in premalignant lesions including low-grade or high-grade dysplastic nodules, indicative of their contribution in early stages of HCC development [14]. Moreover, deregulated miRNAs are shown to be pivotal modulators in tumor progression and aggressiveness, in which they act as oncogenes or tumor suppressors [7].…”
Section: Discussionmentioning
confidence: 99%
“…While miRNAs are directly implicated in physiological processes in the liver, including postnatal growth, regeneration and functioning, their abnormal expression is pivotal in different stages of fibrosis/cirrhosis-associated hepatocarcinogenesis in humans, contributing to sustained cell proliferation, epithelial mesenchymal transition, invasion, metastasis, angiogenesis, and drug resistance hallmarks [8]. In chemically-induced rodent models of fibrosis and hepatocarcinogenesis, the importance of miRNA deregulation is also reported [6,72]. Especially, the DEN/CCl4 approach used recapitulated some miRNomic features of the corresponding human disease, as the downregulation of miR-144-3p and miR-376a-3p, eliciting the translational value of the present short/medium term bioassay.…”
Section: Discussionmentioning
confidence: 99%
“…Most HCC cases (70 -90%) arise in the setting of liver fibrosis/cirrhosis, mainly caused by chronic hepatitis B (HBV) and C (HCV) virus infections, alcoholic liver disease and non-alcoholic fatty liver disease (NAFLD) [3,4]. This malignancy emerges due to the accumulation of multiple molecular alterations, including the deregulation of microRNA (miRNA) expression [5,6]. miRNAs are noncoding, singlestranded molecules of ~22 nucleotides that constitute a class of gene regulators [7].…”
Section: Introductionmentioning
confidence: 99%